Sharia Issues on Loot Boxes in Online Games and Esport - Jusoh Yusoff, Amir Fazlim; Abd Razak, Iffah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Online games and esports have attracted Muslims across Southeast Asia. However, this phenomenon has created some issues pertaining to sharia such as purchasing loot boxes while playing online games. A loot box is a feature in online games that produces microtransactions, which generate income for game providers. It represents a mystery box purchased by players while playing games. The concept of buying loot boxes usually involves a purchase of something unknown to the buyer. Since the item of the purchase is unknown, this study aims to examine sharia ruling on purchasing the loot box in online games. This qualitative study applies content analysis and interviews. It reveals that loot boxes purchase is void according to sharia and impermissible. This is due to the fact that it represents gambling, and the sale is not sharia compliant. This study provides guidelines for sharia-compliant online games and esports for Muslim in Southeast Asia.